2007
DOI: 10.2319/120605-426r.1
|View full text |Cite
|
Sign up to set email alerts
|

Etching Enamel for Orthodontics with an Erbium, Chromium:Yttrium-Scandium-Gallium-Garnet Laser System

Abstract: Objective: To test the shear bond strength, surface characteristics, and fracture mode of brackets that are bonded to enamel etched with an erbium, chromium:yttrium-scandium-gallium-garnet (Er,Cr:YSGG) laser operated at different power outputs: 0.5 W, 1 W, and 2 W. Materials and Methods: Human premolars that had been extracted for orthodontic purposes were used. Enamel was etched with an Er,Cr:YSGG laser system operated at one of three power outputs or with orthophosphoric acid. Results: The shear bond strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
4
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 18 publications
5
57
4
5
Order By: Relevance
“…In contrast to the bur, which wears out substrates such as restorative materials and produces a smear layer, laser ablates the restorative materials without smear layer formation, 10,12 and several studies have shown that Er, Cr: YSGG laser does not produce any smear layer. 8,12,19 Formation of a smear layer makes bonding of the adhesive resins difficult because of its low surface energy. 20 Regarding the AFM data, although there were no significant differences in surface roughness values between laser-treated and bur-ground groups, in the laser-treated group there was a significant increase in surface area compared with the burground group.…”
Section: S-28mentioning
confidence: 99%
“…In contrast to the bur, which wears out substrates such as restorative materials and produces a smear layer, laser ablates the restorative materials without smear layer formation, 10,12 and several studies have shown that Er, Cr: YSGG laser does not produce any smear layer. 8,12,19 Formation of a smear layer makes bonding of the adhesive resins difficult because of its low surface energy. 20 Regarding the AFM data, although there were no significant differences in surface roughness values between laser-treated and bur-ground groups, in the laser-treated group there was a significant increase in surface area compared with the burground group.…”
Section: S-28mentioning
confidence: 99%
“…With the recent introduction of erbium-doped yttrium aluminum garnet (Er:YAG) laser in dentistry for the ablation of hard tissues, including enamel and dentin, laser enamel preparation has been proposed as an alternative to phosphoric acid etching [79]. The Er:YAG laser can effectively modify enamel and dentin surfaces because of its 2.94 mm wavelength emission, which coincides with the main absorption band of water and OH− groups in hydroxyapatite [10].…”
Section: Introductionmentioning
confidence: 99%
“…The ablation of tooth structure is achieved, via a thermomechanical interaction and, since the tissue is not completely vaporised, but only disintegrated into fragments, the majority of incident radiation is consumed in the ablation process, leaving very little residual energy for adverse thermal interactions with the pulp tissue and surrounding soft and/or hard structures. 8,20 Moreover, Er:YAG laser etching is painless and does not involve either vibration or heat, and the easy handling of the apparatus makes this treatment highly attractive for routine clinical use. 13 Also, this laser can be used in wet conditions and the water-cooled system does not cause any untoward thermal effects on the tooth pulp.…”
Section: Discussionmentioning
confidence: 99%